The functional purpose of the antipophora in the information speech (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2010)
The article presents the communicative-pragmatic functions of the antipophora (the rhetorical figure − the question and the answer). The peculiarities and appropriation of the usage of antipophora in the information texts proper and the texts based on the commentaries are also determined here.
Keywords: antipophora; communicative-pragmatic functions; information texts proper; speech based on the commentaries